Size Selective Parasitism of Rainbow Trout (Oncorhynchus mykiss) by Chestnut Lampreys (Ichthyomyzon castaneus) in an Artificial Setting - Jeremiah M. Salinger; Ronald L. Johnson (Southeastern Fishes Council Proceedings, 2020)
Paradigms of optimal resource utilization by animals, both classical and more recent, were not originally developed in the context of parasitism. Though this oversight has slowly been reversed, little attention has been paid to optimal resource utilization by parasitic fishes, such as lampreys. Multiple explanations for host size selection by parasitic lampreys may be plausible, but results from previous studies have been inconsistent. We studied host size selection by Chestnut Lampreys (Ichthyomyzon castaneus) parasitizing Rainbow Trout (Oncorhynchus mykiss) in fish hatchery raceways in north central Arkansas during the late winter and early spring of 2013. Parasitized Rainbow Trout were significantly shorter than non-parasitized conspecifics. Using the relative weight metric of condition, evidence was found that parasitized Rainbow Trout were in better condition than non-parasitized Rainbow Trout. Our findings are not consistent with previous studies of parasitic lamprey host size selection, but do suggest that Chestnut Lampreys are capable of determining a fish’s suitability as a host based on their plumpness even in a setting with low host size heterogeneity and high host density.
Keywords: Chestnut Lamprey; parasitism; optimal resource utilization; relative weight; Rainbow Trout